First record of a cockroach (Insecta: Blattaria: Mesoblattinidae) from the Sinuiju Formation of the Democratic People's Republic of Korea. (August 2021) - So, Kwang-Sik; Won, Chol-Guk; Ri, Chol-Jun; Jon, Su-Hyang
Abstract: Numerous cockroach specimens are found in the materials collected in the Sinuiju Formation from Paektho-dong, Sinuiju City, North Phyongan Province, Democratic People's Republic of Korea (DPRK). Of them, there is Perlucipecta aurea Wei et Ren, 2013, which belongs to the Mesoblattinidae. This discovery not only extends the geographic distribution of Perlucipecta in the Mesozoic but also fills a blank in Mesoblattinidae study in Sinuiju region. Highlights: Perlucipecta aurea is firstly described from the Sinuiju Formation. The remarkable taxon belongs to the family Mesoblattinidae. This fossil show the evidence that the Jehol Biota extended to the Sinuiju area. This new taxon also fills a blank in Mesoblattinidae study in Sinuiju region.